ANALISIS STRATEGI SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN DI BANK MUAMALAT - Salsabilla Putri; Hendra Riofita (Lembaga Pengembangan Kinerja Dosen, 2024)
Human resources (HR) are one of the most important factors that cannot be separated from an organization, both institutions and companies. HR is also the key that determines the development of the company. In essence, HR is in the form of humans who are employed in an organization as drivers, thinkers and planners to achieve the goals of the organization. Today, the latest developments view employees not as mere resources, but rather as capital or assets for institutions or organizations. Literature review is a scientific study that focuses on a particular topic. Literature review will provide an overview of the development of a particular topic. The results of the study stated that Bank Muamalat Indonesia, as the first Islamic bank in Indonesia, has a major role in supporting economic growth based on Islamic values. In the midst of tight competition in the banking industry, the quality of human resources (HR) is a key factor in success. The right HR management strategy not only helps improve operational efficiency but also ensures that sharia principles are met. Therefore, HR management at Bank Muamalat focuses on aspects of recruitment, training, performance management, and employee retention